A cross sectional survey of the barriers for implementing rapid HIV testing among French general practitioners. (October 2016) - Fraisse, Thibaut; Fourcade, Camille; Brazes-Sanz, Julie; Koumar, Yatrika; Lavigne, Jean Philippe; Sotto, Albert; Laureillard, Didier
In France, almost 30, 000 people are unaware of their HIV-positive status. Innovative screening strategies are essential to reach this population. The aim of this study was to describe the acceptability of rapid HIV testing (RHT) among French general practitioners (GPs) working in the south of France and barriers for implementing this strategy. We analysed an anonymous questionnaire sent by mail to GPs about demographic data, routine practice, knowledge of RHT and barriers to its use. Between 1 April and 30 September 2013, out of the 165 GPs contacted, 78 returned the questionnaires. The GPs' mean age was 52 years; 49 were men. Fifty-one GPs reported that their registered patients included at least one HIV-infected person and 70 GPs reported taking care of high-risk patients. Sixty-three percent of GPs reported being interested in using RHT in their daily practice. The main reasons reported by uninterested GPs were: greater confidence in standard HIV testing, difficulties including RHT during the routine consultation, difficulties to screen for other sexually transmitted infections simultaneously, and difficulties to deliver a positive result. French National Authorities for Health propose to screen the population at least once in their lifetime and high-risk people at least once a year. In order to achieve this aim, RHT should be included in the GPs' arsenal for HIV testing. We showed a high acceptability of RHT by GPs. If specific and adapted training is developed, and if solutions to barriers reported by GPs are found, RHT could be implemented in to their routine activity.